2020
DOI: 10.1021/acs.oprd.0c00383
|View full text |Cite
|
Sign up to set email alerts
|

Design and Commercialization of an End-to-End Continuous Pharmaceutical Production Process: A Pilot Plant Case Study

Abstract: The pharmaceutical industry faces multiple challenges (e.g., inefficient manufacturing techniques, quality control issues, and supply chain vulnerabilities) because of its current batch-wise approach to manufacturing. Recent regulatory support for continuous manufacturing and advances in continuous process technologies have caused an increase in interest from some drug manufacturers to modernize their production processes. However, many of these companies have focused on hybrid processes, where only certain st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 50 publications
0
43
0
Order By: Relevance
“…Industry has generally been slow to adopt flow technology due to the "like what you know, know what you like" sentiment and the initial costs of investing in the necessary equipment to replace well established and well optimised processes. Despite this, the pharmaceutical industry is beginning to take advantage of the benefits offered by continuous manufacturing [624][625][626]. Undoubtedly, there are processes currently being used within the flavour and fragrance industry for which flow would offer an attractive alternative with regards to both cost and green/ environmental implications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Industry has generally been slow to adopt flow technology due to the "like what you know, know what you like" sentiment and the initial costs of investing in the necessary equipment to replace well established and well optimised processes. Despite this, the pharmaceutical industry is beginning to take advantage of the benefits offered by continuous manufacturing [624][625][626]. Undoubtedly, there are processes currently being used within the flavour and fragrance industry for which flow would offer an attractive alternative with regards to both cost and green/ environmental implications.…”
Section: Discussionmentioning
confidence: 99%
“…In this example, the aluminium chloride was solubilised in the propionyl chloride (626) and streamed through a coil reactor at 87 °C along with the isobutylbenzene (620). The flow stream was then quenched with HCl to terminate the reaction and avoid clogging of the insoluble aluminium salts.…”
Section: Friedel-crafts Reactionsmentioning
confidence: 99%
“…A second concept, the continuous rotary plate filter (CRPF) was invented as part of an integrated continuous manufacturing pilot plant of Continuus Pharmaceuticals. Recent studies showed the potential of combined filtration and washing in the CRPF as a part of an end-to-end continuous manufacturing process [10,[23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Motivated by the benefits shown in Fig. 1 [6][7][8][9][10], the pharmaceutical industry is transitioning to continuous processes, including end-to-end integrated continuous manufacturing (ICM) approaches [1,6,8,[10][11][12][13][14][15][16][17][18]. A first-of-its-kind research demonstration of an end-to-end ICM line was unveiled by MIT in 2011 [13].…”
Section: Introductionmentioning
confidence: 99%